El temprano impacto de la Revolución Cubana en el movimiento estudiantil argentino. El caso de la Universidad de Buenos Aires. 1959-1962 - Juan Sebastián Califa (Nuevo mundo - Mundos Nuevos, 2013)
The academic literature has demonstrated the early impact the Cuban Revolution had upon Latin America. In Argentina, it is the growing literature devoted to the intellectuals which has been wondering the most about this influx. The pioneering work of Oscar Teran and Silvia Sigal has shown this significant influence on an important intellectual group which was under a process of transformation in the 1960s. In this paper, I will analyze the ideological impact this revolution had on the student movement which, due to the process of left radicalization that it was going through, would begin to increase its effect on the national political scene. To avoid falling into facile generalizations, this paper will focus on the situation at the University of Buenos Aires, the largest university in the country. In particular, I am interested in showing what groups this event affected the most and the different ways in which its influence was perceived. This is necessary in order to refrain from the common and equivocal expression that presupposes the impact of the Cuban process oriented all the youth towards left positions, thus sidestepping the opposite effect.